Scintillation timing characteristics of (La, Gd)2Si2O7:Ce and Gd2SiO5:Ce single crystal scintillators: A comparative study. (September 2016) - Chewpraditkul, Weerapong; Sakthong, Ongsa; Chewpraditkul, Warut; Yawai, Nattasuda; Szczesniak, Tomasz; Swiderski, Lukasz; Moszynski, Marek; Kurosawa, Shunsuke; Murakami, Rikito; Horiai, Takahiko; Yoshikawa, Akira; Nikl, Martin
Abstract: The scintillation timing characteristics of (La, Gd)2 Si2 O7 :Ce (GPSLa23.5%:Ce) single crystal were studied and compared with Gd2 SiO5 :Ce (GSO:Ce) single crystal. The photoelectron yield, scintillation decay times and coincidence time resolution were measured. At 511 keV γ-rays, the photoelectron yield of 10, 770 ± 500 phe MeV −1 and energy resolution of 5.4 ± 0.2% obtained for GPSLa23.5%:Ce are much better than those of 3350 ± 160 phe MeV −1 and 7.8 ± 0.3% obtained for GSO:Ce. The scintillation decay time profile was measured by the time-correlated single photon counting technique using a fast-slow coincidence setup. In both materials the comparable rise times of several nanoseconds are present. The fast component decay time of 56 ns with relative intensity of 49% obtained for GPSLa23.5%:Ce is inferior to that of 32 ns(88%) obtained for GSO:Ce. Consequently, the coincidence time resolution of GPSLa23.5%:Ce is slightly worse than that of GSO:Ce. The normalized time resolution was also discussed in terms of a number of photoelectrons and decay time of the scintillation pulse. Highlights: Scintillation characteristics of GPSLa23.5%:Ce and GSO:Ce were compared. Both crystals showed slow rise-time characteristics in their scintillation pulses. Energy resolution of 5.4% @511 keV was obtained for GPSLa23.5%:Ce. GPSLa23.5%:Ce showed higher contribution of slow scintillation light. Coincidence time resolution of 660 ps was obtained for GPSLa23.5%:Ce.